Correspondence of Florence O’Donoghue with various individuals regarding his book on Tomás Mac Curtain - O'Donoghue, Florence, 1895-1967; Hayes-McCoy, Gerard Anthony, 1911-1975; Dunne, Frank, 1894-; Langford, Riobard, 1896-1978 (1958)
Includes letters from Proinnsias Ó Duinn and G.A. Hayes-McCoy, detailed critiques by Riobaird Langford, and the Cork 1916 Men’s Association, and newspaper cuttings.
Keywords: MacCurtain, Tomás, -- 1884-1920; Irish Republican Brotherhood; Ireland -- History -- War of Independence, 1919-1921; Ireland -- History -- 1910-1921; Ireland -- History -- 1922-